Obstructions for learners in the use of ICT in KSA institutions - Alharbi, Omran (Advances in Social Sciences Research Journal, 2020)
The advancement of digital technology has a great influence on the development of many areas of modern life. Over recent years, e-learning systems have managed to gain a competitive edge over the more traditional methods of learning. The learning and teaching techniques employed by e-learning systems allow more flexibility and provide freedom from the restrictions of time, location, physical presence and other aspects of traditional learning. Nevertheless, e-learning does have its own drawbacks, and research into the barriers to learning will assist in overcoming some of the problems associated with e-learning success. This study attempts to determine the obstacles that can influence the success of ICT within institutions in the Kingdom of Saudi Arabia. This qualitative research examined the obstacles of the use of ICT in the education process from learner’s perspectives and the potential solutions that can help to reduce these obstacles. Semi-structured interviews were conducted with seven e-learning students from one Saudi University. Purposive sample techniques were used with participants, and the results revealed that there were many barriers that hindered learners from benefitting from the use of ICT in education. These obstacles included lack of technical support, technical issues, lack of English language, lack of design e-course materials, and lack of motivation. In addition, a number of solutions were considered in this study.